(untitled) (Bangladesh Journal of Botany, 2015)
A greenhouse test was conducted in 2011 and 2012 growing seasons at Giza Agricultural Research station to evaluate the reaction of six cotton genotypes to Fusarium wilt disease. The genotypes showed considerable variation in susceptibility to the disease (percentage of wilt incidence), which ranged from 32.24 to 88.0% In general, the genotypes could be divided into highly susceptible, susceptible, moderately susceptible, moderately resistant, and resistant. Data for wilt incidence and level or activity of some component biochemicals (phenols, peroxidase, and polyphenoloxidase) were introduced into a computerized linear regression analysis. The analysis constructed seven predictive models by using the biochemical components, singly or in combination, as biochemical predictors. It was evident that models nos. 1 and 5 were the best models for predicting incidence of Fusarium wilt. The superiority of these models was attributed to their high R2 value (0.668 and 0.814, respectively) and the significance of their F. values (p = 0.047 and p = 0.080, respectively). The results of the present study suggest that phenols alone or both phenols and polyphenoloxidase in uninfected cotton seed, which may or may not take part of the Fusarium wilt resistance mechanisms, can use as biochemical markers to predict Fusarium wilt resistance. DOI: http://dx.doi.org/10.3329/bjb.v43i3.21613 Bangladesh J. Bot. 43(3): 353-357, 2014 (December)